Self-Efficacy, Organizational Culture and Quality of Innovation Related to Student Sharing Knowledge - Tyna Yunita (INQUISITIVE : International Journal of Economic, 2021)
The purpose of this study is to analyze the effect of self-efficacy, organizational culture, and quality of innovation on knowledge sharing. The phenomenon of social media as a communication medium becomes a unique attraction for students in the general student environment. This study explores social media that are in high demand and used as a means of student learning. The statistical analysis method used is Structural Equation Modeling (SEM) with a simple random sampling technique with 125 student respondents and students of Universitas Bhayangkara Jakarta Raya. The results of this study indicate that self-efficacy, organizational culture, and quality of innovation have a positive impact on knowledge sharing. From the research findings, organizational culture provides the highest output value for knowledge sharing